Novel Genomic Aberrations in Testicular Germ Cell Tumors by Array-CGH, and Associated Gene Expression Changes - Rolf I. Skotheim; Reija Autio; Guro E. Lind; Sigrid M. Kraggerud; Peter W. Andrews; Outi Monni; Olli Kallioniemi; Ragnhild A. Lothe (Cellular Oncology)
Introduction: Testicular germ cell tumors of adolescent and young adult men (TGCTs) generally have near triploid and complex karyotypes. The actual genes driving the tumorigenesis remain essentially to be identified. Materials and Methods: To determine the detailed DNA copy number changes, and investigate their impact on gene expression levels, we performed an integrated microarray profiling of TGCT genomes and transcriptomes. We analyzed 17 TGCTs, three precursor lesions, and the embryonal carcinoma cell lines, NTERA2 and 2102Ep, by comparative genomic hybridization microarrays (array-CGH), and integrated the data with transcriptome profiles of the same samples. Results: The gain of chromosome arm 12p was, as expected, the most common aberration, and we found CCND2, CD9, GAPD, GDF3, NANOG, and TEAD4 to be the therein most highly over-expressed genes. Additional frequent genomic aberrations revealed some shorter chromosomal segments, which are novel to TGCT, as well as known aberrations for which we here refined boundaries. These include gains from 7p15.2 and 21q22.2, and losses of 4p16.3 and 22q13.3. Integration of DNA copy number information to gene expression profiles identified that BRCC3, FOS, MLLT11, NES, and RAC1 may act as novel oncogenes in TGCT. Similarly, DDX26, ERCC5, FZD4, NME4, OPTN, and RB1 were both lost and under-expressed genes, and are thus putative TGCT suppressor genes. Conclusion: This first genome-wide integrated array-CGH and gene expression profiling of TGCT provides novel insights into the genome biology underlying testicular tumorigenesis.